Pengaruh Kepatuhan Self-Management Terhadap Kualitas Hidup pada Pasien Stroke - Fernandez, Gratsia Victoria; Wirawan, Alfonsius Ade; Sirait, Imelda (Jurnal Pustaka Keperawatan (Pusat Akses kajian Keperawatan), 2026)
The involvement of individuals with stroke in self-management is a key factor in recovery, empowerment, and improved health outcomes, which can ultimately influence their quality of life. The aim of this study was to analyze the effect of self-management adherence on the quality of life among stroke patients. This research was a quantitative study using a cross-sectional design, with purposive sampling and a total sample of 120 stroke patients. Data were collected using the Out-of-Hospital Adherence Questionnaire for Stroke Patients (OHAQ-SP) and the Stroke Impact Scale 3.0 (SIS), and analyzed using the Spearman rank test. The results showed that most respondents were adherent to self-management (76.9%) and had a high quality of life (62.3%), with a significant correlation (p = 0.000; r = 0.833). These findings indicate that self-management adherence has a positive, strong, and significant relationship with the quality of life of stroke patients. The higher the patient’s adherence to self-management behaviors, the higher their quality of life